Antiganglioside antibodies in Guillain-Barré syndrome after a recent cytomegalovirus infection. Issue 3 (1st March 1999) - Khalili-Shirazi, Azadeh; Gregson, Norman; Gray, Ian; Rees, Jeremy; Winer, John; Hughes, Richard
Abstract : OBJECTIVE: To study the association between anti-ganglioside antibody responses and Guillan-Barré syndrome (GBS) after a recent cytomegalovirus (CMV) infection. METHODS: Enzyme linked immunosorbant assay (ELISA) was undertaken on serum samples from 14 patients with GBS with recent cytomegalovirus (CMV) infection (CMV+GBS) and 12 without (CMV-GBS), 17 patients with other neurological diseases (OND), 11 patients with a recent CMV infection but without neurological involvement, 11 patients with recent Epstein-Barr virus (EBV) infection but without neurological involvement, and 20 normal control (NC) subjects. RESULTS: IgM antibodies were found at 1:100 serum dilution to gangliosides GM2 (six of 14 patients), GM1 (four of 14), GD1a (three of 14) and GD1b (two of 14) in the serum samples of the CMV+GBS patients, but not in those of any of the CMV-GBS patients. IgM antibodies were also found to gangliosides GM1, GD1a, and GD1b in one of 11 OND patients, to ganglioside GM1 in one of 11 non- neurological CMV patients, and to ganglioside GD1b in one of 20 NC subjects. Some patients with EBV infection had IgM antibodies to gangliosides GM1 (five of 11), GM2 (three of 11), and GD1a (two of 11). However, the antibodies to ganglioside GM2 had a low titre, none being positive at 1:200 dilution, whereas five of the CMV+GBS serum samples remained positive at this dilution. CONCLUSION: Antibodies to ganglioside GM2 are often associated with GBS after CMV infection, but their relevance is not known. It is unlikely that CMV infection and anti-ganglioside GM2 antibodies are solely responsible and an additional factor is required to elicit GBS.